A Crtitical Review of “Future of maritime education and training: blending hard and soft skills” by Geada Borda de Água et al. - Stevian G. A. Rakka, Stevian (Cipta Kind Publisher, 2024)
This review evaluates an article entitled “Future of maritime education and training: blending hard and soft skills” by Pedro Manuel Geada Borda de Água, Armindo Dias da Silva Frias, Manuel de Jesus Carrasqueira and José Manuel Modas published in the Scientific Journal of Maritime Research. The original article focuses on the integration of 21st century professional skills as soft skills into maritime education and training programmes, while proposingknowledge triangle concept and double-loop learning method to overcome the future challenges of the programmes. While this article is articulated in a thorough and comprehensive review of authors’ opinions, there is not a clear categorization of “soft skills” provided, which clearly encompasses 21st century skills referred in this article. Additionally, this review discusses on some suggestions to improve the review on MHEIs, the knowledge triangle, double-loop learning methods and connection between them comprehensively.Furthermore, the proposal of authors on MET programme based on MarLEM project, which could be improved by adding more variety into the programme as proposed in this review.